Hypertonic dextrose prolotherapy in osteoarthritis: mechanisms, efficacy, and future research directions - Huang, Kai; Cai, Haili (Frontiers in Endocrinology, 2025)
Osteoarthritis (OA) is a degenerative joint disease that causes pain, stiffness, and reduced mobility, significantly affecting the quality of life for millions globally. Current treatments focus on symptom management, with limited efficacy in addressing the underlying disease progression. Hypertonic dextrose prolotherapy (DPT) has emerged as a potential regenerative treatment, utilizing dextrose injections to stimulate the body’s natural healing mechanisms by promoting tissue regeneration, strengthening ligaments, and improving joint function. Recent clinical studies, including the latest research findings, have shown that prolotherapy offers significant pain relief and functional improvement in knee OA, often outperforming other treatments like hyaluronic acid (HA) and corticosteroid injections. Despite promising results, the efficacy of prolotherapy varies across studies due to differences in protocols and study designs. Challenges remain, including lack of standardization, methodological bias, and short-term follow-up. Future research with rigorous designs and long-term follow-ups is necessary to establish prolotherapy’s role in OA management, ensuring a more comprehensive understanding of its therapeutic potential.